(untitled) (Research, Society and Development, 2022)
The aim of the study was to analyze the association between exposure to sedentary behavior (ECS), sleep quality indicators and other health risk behaviors in adolescents in the state of Sergipe, Brazil. This is a cross-sectional epidemiological study with a representative sample of 4139 public school students in Sergipe. Data collection was through the Global Student Health Survey (GSHS, WHO). The outcome variable analyzed in the study was (ECS), considering exposed adolescents with a period ≥ 3 hours a day. Alcohol consumption, drug use, smoking, sleep duration and self-assessment were selected as independent variables, and sex, age and mean family income as control variables. For the association between the variables, binary logistic regression was used. The analysis revealed that the variables sex, age, mean family income, alcohol consumption, drug use and sleep duration were associated with ECS after adjustment. Sleeping eight hours or less a day was shown to be a protective factor for ECS. The study concluded that ECS of students has a high prevalence and association with multivariate factors among adolescents in Sergipe, thus the need for interventions aimed at reducing ECS and other health risk behaviors is evident.